Monotonicity and robustness in Wiener disorder detection. Issue 1 (2nd January 2019) - Ekström, Erik; Vaicenavicius, Juozas
Abstract: We study the problem of detecting a drift change of a Brownian motion under various extensions of the classical case. Specifically, we consider the case of a random post-change drift and examine monotonicity properties of the solution with respect to different model parameters. Moreover, robustness properties – effects of misspecification of the underlying model – are explored.